Analysis of fraudulent financial report from the perspective of a fraud hexagon - M. Faqih Nadhim; Catur Ragil Sutrisno; Dina Amalia Mahmudah (Universitas Pekalongan, 2025)
This study aims to test the effect of the fraud hexagon theory on the Fraudulent Financial Report. The fraud hexagon theory is composed of six elements: pressure, capability, collusion, opportunity, rationalization, and ego. Measurement of elements through variables of financial targets, financial stability, ineffective monitoring, CEO education, political connections, external auditor quality, rationalization, and CEO duality. The population used in the study were State-Owned Enterprises (BUMN) listed on the Indonesia Stock Exchange (IDX) for the period 2017 to 2021. The data used were secondary data in the form of company financial reports. The sampling technique used was purposive sampling, while the analysis technique used was partial least squares structural equality modeling (PLS-SEM). Based on purposive sampling, there were 21 companies selected for five years, or 105 observations, as research samples. This study found that financial targets, financial stability, rationalization, and CEO duality had a positive effect on financial statement fraud, and CEO education, political connections, and external auditor quality were proven to have no effect on financial statement fraud. While ineffective monitoring had a negative effect on financial statement fraud. Theoretically, this study contributes to agency theory and fraud theory for the discussion of financial statement fraud. Practically, this study can be a consideration for current and prospective investors to be more careful in choosing companies to invest in, especially in State-Owned Enterprises (BUMN).